Gestión financiera en el manejo de la liquidez en las asociaciones de residentes de urbanizaciones - Bajaña Ibarra, Fabiana del Carmen (2023)
The research project bases its analysis on Financial Management for the management of liquidity in the Associations of Residents of Urbanizations, which allows optimizing the way of collection, positively influencing the liquidity of the organization, as well as contributing to the construction of a model that allows the optimization of collection management, increase available funds; and, improve the financial presentation of the Associations. Chapter I presents the approach to the problem of Financial Management in the management of liquidity in associations of residents of urbanizations and also justification, general objective and specific objectives established as a reference to the research topic...............